ASPEK PULMONOLOGIS INFEKSI OPORTUNISTIK PADA INFEKSI HIV/AIDS - Agustriadi, Ommy; Sutha, Ida Bagus (journal of internal medicine; Vol. 9, No. 3 September 2008)
Human Immunodeficiency Virus (HIV) known as etiologic agent for AIDS (Acquired Immunodeficiency Syndrome), in which followed or accompanied by certain opportunistic infections and malignancies. Perhaps the most important reason for the frequent development of diverse pulmonary complications in HIV/AIDS relates to the fact that the lung is chronically exposed to both infectious or non-infectious airborne agents (exogenously) and hematogenously spread agents (endogenously) through an expansive surface area consisting of millions of units called alveoli, that infected alveolar macrophages and lymphocytes. The mechanisms that may play role of defected lung defend mechanisms were direct effect of HIV that infected and kill cells cause damaged to the effector cells and shifted cells function from immunostimulative to immunosupressive, then impaired migration capacity of lymphocytes, monocytes or netrophils to lung. In turn, the opportunistic infections easily developed. In almost 65% AIDS patients also accompanied with oppportunistic infections in the lung. Pneumocystis carinii pneumoniae was the most often, followed by M. tuberculosis infection, bacterial and fungal pneumoniae respectively. Whereas, viral pneumoniae was rare
Keywords: opportunistic infections, PCP, HIV, AIDS